Energy efficiency analysis of heterogeneous cellular network based on Thomas cluster process - Minglu JIN; Nan GUO (Tongxin xuebao)
In the existing heterogeneous cellular networks (HCN),the rapid increasing of small cells caused a problem that the hotspots where users were clustered generated a huge amount of energy consumption.To improve the energy efficiency of the networks,the spatial model was researched.The users in hotspots in the HCN were modeled as the Thomas cluster process,combined with the max mean bias received signal power (max-BRP) strategy to achieve base station load balancing,and the user’s association probability,coverage probability and the network’s energy efficiency were derived using tool from stochastic geometry.The simulation shows that the derived formulas are accurate,and the network’s energy efficiency can be greatly improved by setting appropriate bias factors.